2022
DOI: 10.3389/fonc.2022.818860
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Tumor Microenvironment Prognostic Signature for Bladder Urothelial Carcinoma

Abstract: BackgroundThe tumor microenvironment (TME) regulates the proliferation and metastasis of solid tumors and the effectiveness of immunotherapy against them. We investigated the prognostic role of TME-related genes based on transcriptomic data of bladder urothelial carcinoma (BLCA) and formulated a prediction model of TME-related signatures.MethodsMolecular subtypes were identified using the non-negative matrix factorization (NMF) algorithm based on TME-related genes from the TCGA database. TME-related genes with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…RORB has two different isoforms, RORb1 and RORb2, and RORb2 is mainly expressed in retina and pineal gland (78). Recently, studies have found that these two genes play an important regulatory role in the development and progression of various cancers (79)(80)(81). CABP4 has been reported to be associated with the TME of urothelial carcinoma of the bladder currently (79).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RORB has two different isoforms, RORb1 and RORb2, and RORb2 is mainly expressed in retina and pineal gland (78). Recently, studies have found that these two genes play an important regulatory role in the development and progression of various cancers (79)(80)(81). CABP4 has been reported to be associated with the TME of urothelial carcinoma of the bladder currently (79).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, studies have found that these two genes play an important regulatory role in the development and progression of various cancers (79)(80)(81). CABP4 has been reported to be associated with the TME of urothelial carcinoma of the bladder currently (79). RORB can down-regulate the activity of Wnt signaling pathway, thus inhibiting the stemness of gastric cancer cells (82).…”
Section: Discussionmentioning
confidence: 99%
“…First, Kaplan-Meier curves were made to look for differences in prognosis. Moreover, the predictive value was verified by analyzing the time dependence of the receiver operating characteristic (ROC) curves ( Xu et al, 2022a ).…”
Section: Methodsmentioning
confidence: 99%
“…Bladder urothelial carcinoma (BLCA) is a common malignant tumor in the bladder system, which was listed as one of the nine most common cancers by the World Health Organization (WHO). Based on histopathology, BLCA can be classified into two categories, muscle-invasive bladder cancer (MIBC) takes most of the BLCA, which is prone to recurrence, another type that accounts for 30% is non-muscle-invasive bladder cancer (NMIBC) with rapid metastasize and low survival rate ( Xu et al, 2022a ; Kubrak et al, 2022 ). Therefore, we urgently need a prognostic risk model to provide guidance for the treatment of BLCA.…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the lack of effective biomarkers or tools to accurately judge the clinical response and prognosis of patients with BLCA. Therefore, the development and application of various biological detection and informatics techniques to show the difference in prognosis of BLCA patients according to their biological heterogeneity is essential for the treatment of BLCA and improvement of its prognosis [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%